A Grounded Theory Study of Homeopathic Practitioners' Perceptions and Experiences of the Homeopathic Consultation. (30th September 2010) - Eyles, Caroline; Leydon, Geraldine M.; Lewith, George T.; Brien, Sarah
Abstract : Research into the homeopathic consultation has largely focused on patients' experiences, although the practitioner is a crucial component of the therapeutic context and may have an important part in optimizing health outcomes. Therefore the aim of this qualitative research was to gain an in-depth understanding of homeopathic practitioners' perceptions and experiences of the consultation. Medical and non-medical homeopaths were sampled from the registers of the Faculty and Society of Homeopaths. Two phases of data collection were employed. Phase 1 used in depth face-to-face interviews enabling the development of an initial model of the homeopathic consultation. Phase 2 involved observations of homeopathic consultations and practitioner reflective diaries in order to confirm, refute, or enlarge the model. Using the constant comparative method of grounded theory five main categories emerged, exploring the journey, finding the level, responding therapeutically, understanding self, and connecting, forming a model entitled "a theoretical model of a UK classical homeopathic consultation" which describes how homeopaths view and enact the consultation process. This study suggests that the process of identifying and prescribing the remedy is embedded in the consultation, highlighting the interconnectedness of the whole homeopathic consultation and aspects of the consultation that are unique and specific to homeopathy.